Ethylene-mediated nitric oxide depletion pre-adapts plants to hypoxia stress - Hartman, Sjon; Liu, Zeguang; van Veen, Hans; Vicente, Jorge; Reinen, Emilie; Martopawiro, Shanice; Zhang, Hongtao; van Dongen, Nienke; Bosman, Femke; Bassel, George W.; Visser, Eric J. W.; Bailey-Serres, Julia; et al. (Nature communications, 2019)
Timely perception of adverse environmental changes is critical for survival. Dynamic changes in gases are important cues for plants to sense environmental perturbations, such as submergence. In Arabidopsis thaliana , changes in oxygen and nitric oxide (NO) control the stability of ERFVII transcription factors. ERFVII proteolysis is regulated by the N-degron pathway and mediates adaptation to flooding-induced hypoxia. However, how plants detect and transduce early submergence signals remains elusive. Here we show that plants can rapidly detect submergence through passive ethylene entrapment and use this signal to pre-adapt to impending hypoxia. Ethylene can enhance ERFVII stability prior to hypoxia by increasing the NO-scavenger PHYTOGLOBIN1. This ethylene-mediated NO depletion and consequent ERFVII accumulation pre-adapts plants to survive subsequent hypoxia. Our results reveal the biological link between three gaseous signals for the regulation of flooding survival and identifies key regulatory targets for early stress perception that could be pivotal for developing flood-tolerant crops. Plant hypoxia responses are controlled by oxygen and nitric oxide (NO)-dependent proteolysis of ERFVII transcription factors. Here Hartman et al . show that passive ethylene entrapment during root submergence enhances NO-scavenger PHYTOGLOBIN1, ERFVII stability and promotes subsequent hypoxia tolerance.